ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN BODY IMAGE PASIEN KANKER YANG MENJALANI KEMOTERAPI DI RSUP. PROF. DR. R.D. KANDOU MANADO - Wirawan, Alfonsius Ade; Fernandez, Gratsia Victoria; Kambey, Stefan Andrew Glorious Pelealu (Universitas Sam Ratulangi, 2026)
Background: One of the cancer treatments is chemotherapy. However, this therapy has side effects on patients. One of the side effects is body image problems. Patients undergoing chemotherapy are mostly reported to experience negative body image. This can have a negative impact on patients such as psychosocial problems, disruption of daily activities, even affecting well-being and non-fulfillment of patient treatment. Objective: To determine factors related to the body image of cancer patients undergoing chemotherapy. Methods: This study used a quantitative cross-sectional research design. The subjects were 124 cancer patients undergoing chemotherapy. The instruments used were demographic questionnaires, RSE, ZSAS, and BIS. Results: Age and self-esteem are factors that have a statistical relationship with the body image of cancer patients undergoing chemotherapy. The P value of age is 0.048 with an Exp(B) value of 0.682. Meanwhile, the P value of self-esteem is 0.006 with an Exp(B) value of 3.108. Conclusion: Age and self-esteem are significantly related to the body image of cancer patients undergoing chemotherapy. Self-esteem are the most dominant factors influencing body image. Therefore, surgical interventions focused on psychosocial support and self-esteem enhancement, especially in young patients, are necessary to help maintain a positive body image during chemotherapy